Network pharmacology and experimental verification to investigate the mechanism of isoliquiritigenin for the treatment of Alzheimer’s disease - Waimao Gao; Guang Yang; Xinjuan Liu; Kaifan Hu; Jie Pan; Xingyu Wang; Yan Zhao; Ying Xu (Scientific Reports)
Abstract Isoliquiritigenin (ISL), a flavone isolated from licorice, has been demonstrated to exhibit anti-inflammatory and antioxidant properties in the treatment of Alzheimer’s disease (AD). However, the molecular details of the contribution of ISL to AD remain largely elusive. The present study aimed to investigate the molecular mechanisms of ISL against AD. In this study, AD targets and ISL targets were collected via different databases. The overlapped targets between AD and ISL were generated with Venny. Then we performed Gene Ontology (GO) and Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathway enrichment analyses on these common targets. The protein-protein interaction (PPI) network was constructed and clusters were obtained using the Molecular Complex Detection (MCODE) and the Cytohubba plugins. Further, molecular docking study was performed for these core targets. Subsequently, the receiver operating characteristic (ROC) curve analysis and the assessment of hub gene expression levels between AD and healthy individuals were used to estimate a possible link between target genes in AD. Finally, experiments were conducted to verify the therapeutic mechanism of ISL in lipopolysaccharide (LPS)-induced BV2 microglial cells. GO and KEGG pathway analysis found that ISL was significantly enriched in regulation of mitogen-activated protein kinase (MAPK) signaling pathway. The PPI network manifested 7 key targets including albumin (ALB), epidermal growth factor receptor (EGFR), solute carrier family 2 member 1 (SLC2A1), insulin-like growth factor 1 (IGF1), mitogen-activated protein kinase 1 (MAPK1), peroxisome proliferator activated receptor alpha (PPARA) and peroxisome proliferator activated receptor gamma (PPAR-γ, PPARG). Molecular docking showed that ISL had high binding affinity with these key targets. The experimental results revealed that ISL decreased extracellular signal-regulated kinase 1/2 (ERK1/2) phosphorylation and increased the expression of PPAR-γ, and suppressed the production of proinflammatory mediators. Our work revealed that ISL might be an effective treatment strategy in the treatment of AD by its anti-inflammatory effect towards microglia through the ERK/PPAR-γ pathway.